The Role of Electrochemistry and Mineralogy in the Geotechnical Behavior of Salinized Soils - Polivanov, Helena; Barroso, Emilio Velloso; Porto, Rian; Ottoni, Felipe Polivanov; Andrade, Thayssa Pereira (Anuário do Instituto de Geociências, 2021)
The Atterberg limits are essential information and the first step in soil classification for geotechnical purposes. Established laboratory procedures use distilled water in the plasticity and liquid limits determination. However, saline solutions frequently interact with soils in the construction environment through fluid percolation processes. This work aims to understand the variation of the geotechnical behavior of two standard materials with different mineralogical compositions (kaolinitic and smectitic) when affected by NaCl ionic solutions in different concentrations. The purpose is to simulate different soils in environments with the presence of saline solutions. This paper reports an experimental program in which a kaolinite-rich and a smectite-rich material received NaCl solutions in three different concentrations (0.6 %, 3.5 %, and 15.0 %) and had their Atterberg limits determined under these conditions. Additionally, non-contaminated samples of both materials have had their limits measured using distilled water. Physical characterization tests included hygroscopic moisture, grain size distribution, grain density, plastic limit (PL), and liquid limit (LL). These data allowed the determination of the Skempton activity index (AI), plasticity index (PI), consistency index (CI), classification of soils in the Unified Soil Classification System (USCS), and in the Highway Research Board (HRB) with the group index (GI). Mineralogy was determined by X-ray diffraction and physical chemistry by measuring pH in H2O and KCl, determining the ΔpH, the point of zero-charge (PZC), and the surface electrical potential (Ψo). The results show that the pH values rise with increasing salinity, while ΔpH, PZC, Ψo, LL, AI, PI, GI decrease with increasing salinity. The PL decreases with the increase in salinity for smectite and increases for kaolinite. The USCS and HRB demonstrate that the materials start to behave as fewer plastic materials with increased salinity. It is concluded that the variations in the physicochemical parameters of the environment control and modify the geotechnical behavior of the fine-grained soils.